Role of chemokine-like factor 1 as an inflammatory marker in diseases - Li, Yutong; Yu, Haiyang; Feng, Juan (Frontiers in Immunology, 2023)
Chemokines are a class of small molecular weight cytokines that play important roles in immune regulation and cell proliferation and differentiation. Chemokine-like factor 1 (CKLF1) is widely expressed in the human body, especially in peripheral blood leukocytes. CKLF1 can act on various downstream signal transduction pathways, exert a broad spectrum of chemotactic activities, mediate immune inflammatory responses, and promote cell proliferation and migration. As an inflammatory marker, CKLF1 is closely related to the development of autoimmune diseases, tumors, and several other conditions. The application of CKLF1 inhibitors such as IMM-H004 can help delay the progression of these diseases. C19 peptide, a secreted form of CKLF1, may play a protective role against disease pathogenesis. This review article introduces the structure and function of CKLF1 in detail, expounds the signal transduction pathway mediated by CKLF1 and its role in diseases, which is helpful in understanding the pathogenesis of CKLF1-related diseases, and provides new strategies for the targeted therapy of diseases.